1965
DOI: 10.1073/pnas.54.5.1310
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of immune hemolysis by an interaction between red cell-sensitizing antibody and gamma-globulin allotype antibody.

Abstract: central pool. For this reason it was expected that after the introduction of 10 mM xylocaine in the distal pool the downward peak would become a large downward phase (id, Fig. 3, 13-24). However, the secondary action of the anesthetic developed so rapidly that only the deflection resulting from decremental conduction in the first gap remained (Fig. 3, 16; ef. ref. id). For the same reason only trapezoidal action potentials appear in Figure 3, 17-20. The presentation of the theory of the isolated fiber will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1966
1966
1975
1975

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…It has been reported that anti-allotype antiserum may, at certain concentrations, enhance the number of plaques when incubated with the cells to which it is directed (8,52). However, incubation of the antibody-forming cells with the diluted anti-allotype antiserum generally results in an inhibition of plaque formation (8,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that anti-allotype antiserum may, at certain concentrations, enhance the number of plaques when incubated with the cells to which it is directed (8,52). However, incubation of the antibody-forming cells with the diluted anti-allotype antiserum generally results in an inhibition of plaque formation (8,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, imrnunocytes are differentiated so as to synthesize exclusively antibody of one given antigen-specifidty (1-10), biological activity (11,12), and immunoglobulin class or subclass (4,(12)(13)(14)(15). Specialization of imrnunocytes is so extreme that only one allotypic variant of a particular immunoglobulin subclass is produced by cells possessing the genetic information for two variants (16)(17)(18). Identification of the source of the diversity among irnrnunocytes is a major goal in immunology, since it bears upon the instructive and selective theories of antibody formation.…”
mentioning
confidence: 99%
“…The indirect hemolytic plaque test detecting 7S-producing cells (14)(15)(16) was carried out according to Dresser and Wortis (15). A high degree of inhibition of 19S plaques was found when using our unabsorbed rabbit-anti-mouse 7S antiserum confirming the findings of others (15).…”
mentioning
confidence: 99%